Simultaneous Hydrogen and Ethanol Production from Crude Glycerol by a Microbial Consortium Using Fed-Batch Fermentation - Sanjeet Mehariya; Antonella Signorini; Antonella Marone; Silvia Rosa (Energies, 2023)
Simultaneous bioproduction of hydrogen and ethanol from cheaper waste feedstock has the potential for the development of a more cost-effective biofuel generation process. Crude glycerol (CG), a by-product of the biodiesel industry, is a renewable resource, abundant, sold at low prices and available worldwide. However, the main CG limitations in fermentation processes are mainly related to the presence of impurities and the lack of nitrogen sources, both acting on microbial activity. In this study, a fermentation process with CG was improved using a highly specific microbial consortium called GlyCeroL (GCL). The process was developed in fed-batch fermentation mode using not diluted substrate and carried out under non-sterile conditions and at increasing amounts of the substrate (from 20 to 80 gL−1 of glycerol). The results showed higher H2 (from 6 to 8 LL−1) and EtOH (from 13 to 20 gL−1) production by increasing glycerol concentration from 20 to 40 gL−1. On the other hand, a decrease in glycerol degradation efficiency (from 75 to 56%) was observed. Then, the nitrogen sparging strategy was applied. Using CG of 40 gL−1, process improvement was achieved, leading to the increased production of hydrogen (10 LL−1) but not that of ethanol (20 gL−1). A further increase to 60 gL−1 of glycerol produced a slight increment of EtOH (21 gL−1) and H2 (11 gL−1) but a sharp decrease in glycerol degradation efficiency (41%). Acetate, as the main impurity of CG, was an additional carbon source for GCL microorganisms contributing to EtOH production and increasing that of lactic acid to restore the redox balance. The Denaturing Gradient Gel Electrophoresis (DGGE) fingerprint at the end of all fed-batch fermentations supported the robustness of GCL functional units and their adaptability to fermentation conditions.